Evaluation of Seismic Rupture Models for the 2011 Tohoku-Oki Earthquake Using Tsunami Simulation - Ming-Da Chiou; Emmy Tsui-Yu Chang; Sen Jan (Terrestrial, Atmospheric and Oceanic Sciences, 2013)

(untitled)
Developing a realistic, three-dimensional rupture model of the large offshore earthquake is difficult to accomplish directly through band-limited ground-motion observations. A potential indirect method is using a tsunami simulation to verify the rupture model in reverse because the initial conditions of the associated tsunamis are caused by a coseismic seafloor displacement correlating to the rupture pattern along the main faulting. In this study, five well-developed rupture models for the 2011 Tohoku-Oki earthquake were adopted to evaluate differences in simulated tsunamis and various rupture asperities. The leading wave of the simulated tsunamis triggered by the seafloor displacement in Yamazaki et al. (2011) model resulted in the smallest root-mean-squared difference (~0.082 m on average) from the records of the eight DART (Deep-ocean Assessment and Reporting of Tsunamis) stations. This indicates that the main seismic rupture during the 2011 Tohoku earthquake should occur in a large shallow slip in a narrow range adjacent to the Japan trench. This study also quantified the influences of ocean stratification and tides which are normally overlooked in tsunami simulations. The discrepancy between the simulations with and without stratification was less than 5% of the first peak wave height at the eight DART stations. The simulations, run with and without the presence of tides, resulted in a ~1% discrepancy in the height of the leading wave. Because simulations accounting for tides and stratification are time-consuming and their influences are negligible, particularly in the first tsunami wave, the two factors can be ignored in a tsunami prediction for practical purposes.